Tendência temporal da desigualdade nos fatores de risco para doenças crônicas não transmissíveis entre adultos brasileiros de 2007 a 2016 - Dulgheroff, Pedro Toteff (2019)
Noncommunicable chronic diseases are one of the main causes of death in the world and in Brazil. Studies show that the distribution of both deaths and risk factors is unequal among different social levels, with greater burden on the poorest. In Brazil, although some social pol-icies have been implemented focusing on the most vulnerable groups, there is no evidence on the tendency of inequality for the main risk factors. This study aimed to evaluate the trend of social inequality for systemic arterial hypertension (SAH), diabetes mellitus (DM), smoking and obesity, from 2007 to 2016, based on three equity stratifiers: schooling, gender and skin color of the adult population living in Brazilian capitals. Data from 2007 to 2016 were used from the Survey of Risk Factors and Protection for Chronic Diseases by Telephone Survey conducted by the Ministry of Health of Brazil. Inequality was assessed using the slope index of inequality (SII) and the concentration index (CIX). The trend of inequality was estimated by the Prais-Winstern method. Analyzes were performed using STATA / SE® 12.1 software. The risk factors was concentrated in the least educated groups, since the SII and the CIX var-ied between 0 and -20. The inequality decreased for SAH in all analyzes, both by SII (9.8%) and by CIX (41.4%), except for whites and males according to SII, where there was no change. There was an increase in the inequality for DM (21.3%) analyzing the SII, while the CIX showed maintenance of the inequality concentration in the period, with reduction only in females (18.9%). For smoking, there was an increase in inequality according to the CIX (85.2%), except for males where inequality remained constant in the period. According to the SII, smoking inequality increased only among whites (235.7%). There was no change in ine-quality in relation to obesity. We concluded that in Brazil the risk factors for NCDs affect the poor most pronouncedly and that overall, over the last ten years, there has been a reduction in inequality only for SAH, an increase in DM and smoking and an maintenance for obesity. Further studies should explore the possible cause of the observed increased inequality in some of the risk factors analyzed in order to guide social policies and programs targeting the most vulnerable groups.